Animal rights - Hurley, Jennifer A., 1973- (San Diego : Greenhaven Press, 1952)
Presents opposing viewpoints about animal rights, discussing their capacity to suffer, the question of whether they can be the property of people, whether they should be used as food, and animal experimentation.
Includes bibliographical references (p. 101-108) and index.
Keywords: Animal rights -- Juvenile literature; Animal welfare -- Juvenile literature; Animal rights; Animal welfare